2017
DOI: 10.1371/journal.pgen.1006760
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of red blood cell traits in Hispanics/Latinos: The Hispanic Community Health Study/Study of Latinos

Abstract: Prior GWAS have identified loci associated with red blood cell (RBC) traits in populations of European, African, and Asian ancestry. These studies have not included individuals with an Amerindian ancestral background, such as Hispanics/Latinos, nor evaluated the full spectrum of genomic variation beyond single nucleotide variants. Using a custom genotyping array enriched for Amerindian ancestral content and 1000 Genomes imputation, we performed GWAS in 12,502 participants of Hispanic Community Health Study and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 70 publications
(76 reference statements)
2
55
0
Order By: Relevance
“…Due to the relatively small number of Hispanic/Latino individuals with blood cell trait data in TOPMed freeze 5b (n~1,080), including only one heterozygote carrier of rs11549407 in those with blood cell traits measured, we were unable to perform a well-powered replication of the association of rs11549407 with HGB and HCT. Moderate anemia is known to occur in some individuals with thalassemia minor, however, concordant with our results(38).The association of the HBB missense (p.Glu7Lys) variant 11:5227003:C:T or rs33930165 with higher total WBC (β =0.28 and p=8.1x10 -12 ) among AA was unexpected; rs33930165 has been associated with red blood cell indices such as mean corpuscular hemoglobin concentration(20) but not with white blood cell traits. Because of the higher allele frequency of this variant and also the larger number of AA samples (n=6,743) in TOPMed freeze 5b, we were able to replicate this HBB rs33930165 association with total WBC in an independent sample (β=0.27 and p=4.6x10 -4 ) of AA individuals.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Due to the relatively small number of Hispanic/Latino individuals with blood cell trait data in TOPMed freeze 5b (n~1,080), including only one heterozygote carrier of rs11549407 in those with blood cell traits measured, we were unable to perform a well-powered replication of the association of rs11549407 with HGB and HCT. Moderate anemia is known to occur in some individuals with thalassemia minor, however, concordant with our results(38).The association of the HBB missense (p.Glu7Lys) variant 11:5227003:C:T or rs33930165 with higher total WBC (β =0.28 and p=8.1x10 -12 ) among AA was unexpected; rs33930165 has been associated with red blood cell indices such as mean corpuscular hemoglobin concentration(20) but not with white blood cell traits. Because of the higher allele frequency of this variant and also the larger number of AA samples (n=6,743) in TOPMed freeze 5b, we were able to replicate this HBB rs33930165 association with total WBC in an independent sample (β=0.27 and p=4.6x10 -4 ) of AA individuals.…”
supporting
confidence: 89%
“…Second, these traits have family-based heritability estimates in the range of 40-65% (12,13), and have been highly fruitful for gene-mapping with >2700 common and rare variants identified, though primarily in individuals of European ancestry (14)(15)(16)(17)(18)(19). Third, these traits remain under-studied in admixed AA and Hispanic/Latino populations, despite evidence for the existence of variants with distinct genetic architecture in AAs and Hispanics/Latinos (20)(21)(22). For example, while hundreds of variants identified in genome-wide association studies (GWAS) of WBC in individuals of European descent explain only ~7% of array heritability, the African specific Duffy null variant DARC rs2814778 alone accounts for 15-20% of population-level WBC variability in AAs (23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample sizes ranged from 11,809 to 12,705. GWASs for blood count traits in the HCHS/SOL were reported in Hodonsky et al (2017), Jain et al (2017), and Schick et al (2016), and GWASs for blood pressure (BP) traits were reported in Sofer, Wong, et al (2017).…”
Section: Gwass In the Hchs/solmentioning
confidence: 99%
“…With regard to bioinformatic characterization for functional candidate SNP evaluation, eQTL analysis—while insufficient as the sole determinant of tissue specificity—is an important component for ascertaining functional status of candidate variants. Finally, the Metabochip design emphasized regions identified for cardiometabolic traits, so overlap with RBC-trait associations was coincidental; we therefore could not examine generalization or fine-mapping in several well established RBC trait associations, including HBS1L/MYB , LUC7L/ITGF3, HBA1/2 , and HBB 17; 18; 21; 74 .…”
Section: Discussionmentioning
confidence: 99%